Pelaksanaan Polisi Pemilikan Rumah Warga Asing di Wilayah Pembangunan Iskandar Malaysia - Hasni, Ras Amira; Masram, Haidaliza; Md Yassin, Azlina (Research in Management of Technology and Business, 2021)
Iskandar Malaysia Development Region is a development corridor in southern Johor which has a major impact on the country's economic growth. However, development that exceeds demand has resulted in many overhang residential property where H12020 indicates that, Johor recorded the highest state with a total of 3,891 units of unsold property consisting of luxury cost houses with a selling price exceeding RM600,000 per unit. From 2002 until now, the government has introduced foreign ownership policies to increase the ability of foreigners to purchase residential properties in Malaysia.However, there is still doubt about the effectiveness and implementation issues of this policy. Therefore, the objective of this study is to examine its acievement and issues related to the implementation of home ownership policies for foreigners in IM. This study uses a mixed method approach that is quantitative and qualitative method. Quantitative data was analysed using descriptive analysis while qualitative data was analysed using thematic analysis. Study indicated that the achievement of the policy is rather promising with the mean number of property transactions after the policy is implemented is 1,428 units compared to before it takes effect which is at 423 unit. Meanwhile, main issue perceived by foreigners is on the lack of promotion and its complicated policy procedure. While, from the perspective of government consisting of KPKT and MOTAC, the main issue identified is massive objection from locals on the implementation of the policy.